Review of Islamic Law on Religious Moderation of Tariqah Syadziliyah Students in Putatsari Village, Grobogan Regency, Central Java (Program Studi Hukum Keluarga Islam, 2024)
This research aims to explore and explain the practice of religious moderation of Syadziliyah Tariqah students in Putatsari Village, Grobogan Regency, Central Java, the obstacles and solutions taken in improving moderate attitudes among Syadziliyah Tariqah santri, which are then analyzed with an Islamic legal approach. According to the characteristics of the problem studied, the writing of this article is included in the type of field research with a qualitative approach of a sociological nature. The data sources used are primary data and secondary data. Primary data is obtained from in-depth interviews with Syadziliyah Tariqah students and Mursyid, while secondary data is in the form of a literature study. After the data is obtained, it is then analyzed using descriptive analysis techniques. The results showed that the weak knowledge of religious sciences among Syadziliyah Tariqah students gave birth to a less moderate attitude in the appreciation of Tariqah and Sufism due to the many Tariqahs adopted with different qibla of Tariqah murshid so that it becomes an obstacle in itself. The solution in overcoming these obstacles is that the students should have only one murshid and should not branch out. Furthermore, the students before their allegiance are given knowledge and understanding of the essence of the purpose of Tariqah so that they have an inclusive attitude in becoming a salik.